Entre a formação na escola e a formação como atleta de futebol profissional: prioridades e influências - Fabiano Bossle; Lucas Oliveira de Lima (Universidade Estadual do Oeste do Paraná, 2013)
This study has as its main objective verify what representations high performance football athletes from basic categories of two traditional clubs of Porto Alegre have on school and football. In a complementary manner, ascertain what are the priorities of these youngsters in the present moment and what influences they undergo in choosing (prioritizing) between school and football. For this purpose, eight interviews with these athletes, ranging from 13 to 17 years of age, were carried out. The accounts of the athletes showed initially that they think of school as what we call a plan B and football athlete training as a priority. The biggest influence they undergo whether to give greater dedication towards school or football comes from the family. The main representations were: school as an accessory towards the desired career as a professional footballer and football as the dream (everything).